Sustainable-ERP system: A preliminary study on sustainability indicators - Hasan, Muhammad Syahid; Ebrahim, Zuhriah; Wan Mahmood, Wan Hasrulnizzam; Ab Rahman, Mohd Nizam (Penerbit Universiti Teknikal Malaysia Melaka, 2017)
The purpose of this paper was to identify the indicators for sustainability performance that were integrated into the Enterprise Resource Planning (ERP) system. It is crucial for a manufacturing company to embed the sustainability elements into their performance indicators in order to be sustainable in the economic, social, and environment dimensions. In this study, a set of criteria has been used to explore the sustainability indicators through a thorough literature study of related sustainability issues discussed in Scopus Index journals from year 2007 until 2016. In this regard, the indicators were clustered based on their respective sustainability dimensions (i.e. economy, social, and environment). Pareto charts were developed for the analysis process. The most frequent sustainability indicators can be determined based on Pareto 80-20 rule. Results of the analysis showed that from an initial 63 sustainability indicators, 32 indicators were listed as highly influential sustainability indicators. The findings of this study provide an early insight for researchers and industrial practitioners in selecting the most significant sustainability indicators to be integrated into their ERP system.